Analysis of the Current State of Social Entrepreneurship Development in Kazakhstan - A. M. Yerzhanova; L. Z. Ashirbekova; Ja. Korpysa (Экономика: стратегия и практика)
One of the ways of state social growth is to create new jobs for people with disabilities in public administration. One of the most successful and competitive policies in this direction is the development of social entrepreneurship. Today, social entrepreneurship is receiving a lot of attention at the global level. Nevertheless, the theory of social entrepreneurship is still at the conceptualisation stage, as different countries have different features of social entrepreneurship coverage and different approaches to social entrepreneurship initiatives. The government of Kazakhstan has shown interest in the development of entrepreneurship in general and social entrepreneurship in particular as a means of achieving sustainable development goals and solving social problems. Analysing the works of many authors, the paper identified the main characteristics and factors that define social entrepreneurship. The paper conducted regression analysis in order to analyse the current state of social entrepreneurship in Kazakhstan and determine its impact on socio-economic indicators. Kazakhstan faces various social problems such as unemployment, poverty and regional disparities. Social entrepreneurship is seen as a viable approach to solving these problems by creating innovative solutions. The aim of the article is to analyse theoretical and empirical research, to bring together different points of view on the topic of social entrepreneurship and to identify opportunities for its development by analysing the situation of «social entrepreneurship» in Kazakhstan. The scientific novelty of the study is determined by the correlation between the indicators of economic development and social entrepreneurship.